2022
DOI: 10.3390/jcm11216385
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on Head and Neck Cancer Advancement Measured by Increasing Numbers of Urgent Dyspnea Cases—What Could Be Improved in the Event of Subsequent Pandemics?

Abstract: The COVID-19 pandemic has altered all aspects of the healthcare system’s organization and impacted patients with head and neck cancer (HNC) who have experienced delayed diagnosis and treatment. The pandemic resulted in the admission of patients with severe dyspnea and a need for tracheotomy due to extremely advanced HNC. This study’s objective was to evaluate the clinical characteristics of two multi-center cohorts, “pre-COVID-19” and “COVID-19”, of HNC patients admitted as emergencies for dyspnea. The therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
(38 reference statements)
0
5
0
Order By: Relevance
“…Delayed diagnosis of HNC is particularly concerning given that these tumors can double in volume and show nodal progression in as little as one month ( 5 ). Single- and multi-center studies from around the world have reported increases in more advanced HNC stage, tumor size, node involvement and/or metastatic disease among these patients as well as increases in emergency presentation during the COVID-19 pandemic ( 6 12 ). Population-based analyses have found conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed diagnosis of HNC is particularly concerning given that these tumors can double in volume and show nodal progression in as little as one month ( 5 ). Single- and multi-center studies from around the world have reported increases in more advanced HNC stage, tumor size, node involvement and/or metastatic disease among these patients as well as increases in emergency presentation during the COVID-19 pandemic ( 6 12 ). Population-based analyses have found conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the short duration of the study (three years) allowed for uniformity in the main patient evaluation criteria. The sample size was also negatively affected by its significant overlap with the pandemic period, during which strict limitations were placed on the performance of non-urgent surgical procedures [ 34 ], despite the fact that these choices led to a general worsening of disease stages, particularly in neoplastic diseases [ 35 ]. Nevertheless, we believe that limiting the study to the evaluation of only TH, excluding the definitive form, allowed us to analyze a complication that has unique characteristics and causative mechanisms, which we thus aimed to emphasize.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic caused significant strain on healthcare resources globally and influenced the care of all patients, including those with cancer [ 13 , 14 , 15 ]. In the field of neuro-oncology, numerous guidelines recommended the prioritization of high-grade gliomas in the face of potential severe strains on neurosurgical resources and recommended appropriate adjuvant therapy while trying to minimize the risk of COVID for both patients and healthcare providers [ 7 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar trends were observed for patients with other cancers during the COVID pandemic. One study reported a substantial increase in breast cancer patients presenting at an advanced stage compared to a pre-pandemic cohort in Brazil [ 17 ], while another showed increased morbidity from larger tumor size in patients with head and neck cancers [ 15 ]. These trends are thought to represent a delay in presentation to hospitals during COVID, perhaps due to fear of contracting COVID or general recommendations to avoid hospital visits when possible [ 18 ].…”
Section: Discussionmentioning
confidence: 99%